Macroeconomic and Labor Market Impact of Russian Immigration in Israel - Sarit Cohen; Chang-Tai Hsieh (Bar-Ilan University, Department of Economics, 2001)
From the end of 1989 to 1997, over 710 thousand Russian Jews emigrated to Israel, increasing Israel-s working-age population by 15 percent. This paper argues that a canonical one-sector neoclassical growth model explains both the short run and the medium run response of Israel,s economy to this shock. Specifically, we show that average effective wages of native Israelis fell and the return to capital increased during the height of the influx in 1990 and 1991. By 1997 however, both average wages and the return to capital had returned to pre-immigration levels due to an investment boom induced by the initial increase in the return to capital. As predicted by an intertemporal model of the current account, the investment boom was largely financed by external borrowing. Furthermore, despite the high educational levels of the Russian immigrants, the Russian influx did not lower the skill-premia of native Israelis. We show that this result is not explained by Rybczynski-type output composition changes but because the Russian immigrants suffered from substantial occupational downgrading in Israel and thus did not change the relative supply of skilled workers in Israel.
Keywords: 330